Perception of inconvenience costs: Evidence from seven ferry services in Norway. (May 2019) - Díez-Gutiérrez, María; Tørset, Trude
Abstract: Transport projects are assessed mainly by cost-benefit analysis (CBA). Despite its wide use, this method has some weaknesses, such as using simulated traffic volumes as an input. These traffic volumes for future projects are estimated according to user travel patterns based on the new generalised costs (GC), which include travel time, distance, and direct costs. Nevertheless, many large transport projects dramatically change accessibility; thus, other factors could play important roles in the process. Notably, ferry replacement projects reduce travel times, eliminate waiting times, and provide a reliable and flexible connection 24/7. Some of these changes, known as inconvenience costs (IC), are not included in the GC. This study contributes to the scarce literature on the IC concept and relates IC to the factors that different users value. The results, which are based on 9, 878 answers from onboard ferry surveys in 2011 and 2016, revealed that inconvenience factors, such as trip planning and the lack of accessibility to family/friends, leisure activities and a broader labour market, are important. Thus, projects that improve these factors might trigger additional changes in user travel patterns. Four partial proportional odds models were estimated to relate the inconvenience factors to the trip and the socioeconomic features of users. The results showed that the waiting time, frequency of trips via the connection, trip purpose, gender, age and income played important roles in the perception of different factors. In addition, a quantification of the differences in the perceptions among the categories of the variables was described based on the average marginal effects (AME). Highlights: Inconvenience costs (IC) are related to large projects that change accessibility. IC trigger changes in user travel patterns. These changes vary according to trip and socioeconomic characteristics. Including IC in traffic simulations could improve project assessments.